Routledge handbook of environment and society in Asia
1 online resource (xvi, 475 pages)
Keywords: "Nowhere is the connection between society and the environment more evident and potentially more harmful for the future of world than in Asia. In recent years, the rapid development of countries with very large populations has led to a huge increase in environmental problems. This handbook provides a comprehensive survey of the cultural, social and policy contexts of environmental change across East Asia. As climate change related threats to society increase, the book strongly argues the need for increased environmental consciousness in Asian societies. This book is an essential companion for students, scholars, policy makers and researchers working on environmental issues in Asia"--